A pre- and post-course survey of an elective Chinese medicine curriculum among junior Western medical students in Taiwan - Sunny Jui-Shan Lin; Shung-Tai Ho; Yi-Chang Su; Chien-Sung Tsai; Shu-Meng Cheng; Cheng-Yi Cheng; Tso-Chou Lin; Chien-Jung Lin (BMC Complementary Medicine and Therapies)
Abstract Background Demonstrating a positive impact of educational programs on clinical care outcomes is challenging. We assess students' knowledge, attitudes, and behaviors as short-term outcomes of integrating a structured Traditional Chinese Medicine course within a Western medical school. Methods A prospective questionnaire survey was conducted among first-year and second-year undergraduate medical students who participated in the “Introduction to Chinese Medicine” course in 2020. The survey assessed their knowledge, attitudes, and behaviors before and after completing the 32-hour course. Results In total, 89 participants who completed both pre- and post-course questionnaires exhibited significantly higher scores in Chinese medicine knowledge after the course (3.82 ± 0.67 vs. 4.05 ± 0.73, p = 0.002). The majority of medical students displayed positive attitudes towards traditional Chinese medicine (80.9% vs. 83.3%, p = 0.392), particularly regarding the statement, “Traditional Chinese medicine emphasizes holistic considerations and whole person health to a greater extent than Western medicine does” (75.3% vs. 88.8%, p = 0.017). Additionally, most medical students reported proactive behaviors related to integrative care with Chinese medicine, including inquiring about Chinese medicine therapy history (76.4%), the concurrent use of Western and Chinese medications (78.7%) and participating in academic exchanges with Chinese medicine physicians (78.7%) after the course. More medical students expressed an intention to proactively learn more about Chinese medicine after the course (40.4% vs. 51.7%, p = 0.031). Conclusions The elective “Introduction to Chinese Medicine” course enhanced Taiwanese Western medical students’ knowledge of Chinese medicine, fostered positive attitudes towards integrative healthcare involving Chinese medicine, and increased their willingness to learn more about Chinese medicine for future clinical practice. Trial registration Registration prior to patient enrollment was not applicable because participants were not assigned to treatment groups in this study.